Atopy and aporia: undead bodies in fiction - Gama-Khalil, Marisa Martins (Revista de Letras, 2018)
Monsters have always figured in the role of characters in literature, representing not only what should be feared but also, in many cases, which is fearful and terrible that settles in us, hiding behind social masks. After a period of a huge emergency of vampires in literature, film, graphic novels and other media, we see the irruption of an art in which the thematized and problematized monster is the zombie. Some questions emerge, such as: What conditions favor the irruption of narratives with the undead in our contemporaneity? How can we think of the subjectivity of contemporary man on the basis of the undead bodies? What does it mean not to die? We will conduct our analytical course based on some films, a graphic novel and some literary narratives, with special focus on the short story entitled “The pyrotechnician Zachary”, by Murilo Rubião. In the theoretical directions, we will privilege the debate on some notions, such as death, biopolitics, corpse, subjectivity; as well as on concepts from the field of fantastic literature.